Equivalence of background and bleaching desensitization in isolated rod photoreceptors of the larval tiger salamander (The Rockefeller University Press, 1996)
Psychophysical experiments have shown an equivalence between sensitivity reduction by background light and by bleaches for the human scotopic system. We have compared the effects of backgrounds and bleaches on the light-sensitive membrane-current responses of isolated rod photoreceptors from the salamander Ambystoma tigrinum. The quantum catch loss was factored out from the desensitization due to bleaching to give the fraction of "extra" desensitization due to adaptation. For backgrounds, desensitization is well described by the Weber/Fechner equation. The extra desensitization after bleaches can also be described by the Weber/Fechner equation, if an "equivalent" background produced by bleaching is made linearly proportional to the fraction of pigment bleached. A background which produces an extra desensitization of a factor of two is equivalent to a fractional bleach of approximately 6%. Equivalent background and bleaching desensitizations were associated with similar reductions in circulating current. There is a linear relation between log flash sensitivity and decrease in circulating current. Equivalent background and bleaching desensitizations were associated with similar increases in cGMP phosphodiesterase and guanylate cyclase activity. These were inferred from membrane current changes after steps into lithium or IBMX solutions. There were also similar reductions in the integration times of dim flash responses for equivalent desensitizations produced by backgrounds and bleaches. These results suggest that the equivalence between background and bleaching found psychophysically may arise at the very earliest stages of visual processing and that these two processes of desensitization have similar underlying mechanisms.